International management behavior - Lane, Henry W.; Maznevski, Martha L.; DiStefano, Joseph J. (Malden, MA : Blackwell Business, 2000)
This book is about: Intercultural effectiveness in global management; Implementing strategy, structure, and systems; Corporate social behavior in a global economy: competing with integrity; ...
Keywords: Management; International business enterprises; Organizational behavior; International business enterprises -- Management; Culture